Evaluating the Relationship between Physiological Parameters and Performance of Female Swimmers in the 200 m Individual Medley - Gayen, Rajarshi; Tiwari, Sandhya; Tiwari, Sandeep (Physical Education Theory and Methodology, 2025)
Objectives. The primary objective of this study was to evaluate the selected physiological parameters and performance of female swimmers in the 200 m individual medley, analysing the contribution of selected physiological variables and construction of predictive model. Materials and Methods. The study involved forty female swimmers, who were recruited from the state of West Bengal, India. This selection specifically targeted individuals who had actively engaged in the demanding disciplines of the 200 m individual medley swimming events. Furthermore, subjects were carefully selected from the age group spanning 17 to 25 years. After quantifying physiological parameters, swimmers performed a 200 m individual medley test. A value of α = 0.05 was used for all tests as the criterion to determine the presence or absence of significance. Pearson’s product moment correlation coefficient (r) was used for assessing the various relationships of the selected variables towards the performance in the 200 m individual medley. Results. A significant relationship was found between VO2max (r = -0.562), body fat percentage (r = -0.643) and swimming performance in the 200 m individual medley event at the 1% significance level. Multiple linear regression was used for evaluating the contribution of identified physiological variables and construction of predictive model. The regression equation was found to be reliable, as demonstrated by the value of r2 being 0.54. The two independent variables explain 54.00 % variations in the 200 m individual medley event among female swimmers. Conclusions. The F-value for the regression model was determined as highly significant, indicating the reliability of the model. This study provides a further understanding of the physiological variables associated with skilled performance in the women’s 200 m individual medley event, which coaches should consider when training less skilled female swimmers.